Urinary 6-sulfatoxymelatonin level and breast cancer risk: systematic review and meta-analysis - Jing Xu (Nature Portfolio, 2017)
Abstract 6-Sulfatoxymelatonin (aMT6s) is the main metabolite of melatonin in urine, and is a reliable surrogate biomarker reflecting the blood melatonin concentration. This meta-analysis assessed the association between urinary aMT6s level and BC incidence. The electronic databases PubMed, EMBASE, Cochrane Library, and Web of Science were searched. Risk ratios (RRs) were adopted to estimate the relative BC incidence. A total of 7 prospective case-control publications were included, and 6 of them were distinct studies. Pooled analysis of data from the 6 studies involving 1824 women with incident BC and 3954 matched control participants with no overlapping of subjects among studies indicated no significant association between the highest levels of urinary aMT6s and the incidence of BC (RR = 0.97, 95% CI, 0.88–1.08, P = 0.56). Negative associations were observed in postmenopausal women (RR = 0.88, 95% CI, 0.75–1.02, P = 0.10), estrogen receptor positive BC (RR = 0.83, 95% CI, 0.64–1.07, P = 0.15), and studies using 12-hour overnight urine (RR = 0.81, 95% CI, 0.61–1.07, P = 0.13), all with borderline significances. Lag time or invasive degree did not interfere with the results. There was no evident publication bias detected by the Egger’s test and the funnel plot. Conclusively, the current evidence did not support a significant association between urinary aMT6s level and BC risk.